VISUAL COMMUNICATION IN THE DIGITAL AGE: A CONTEXTUAL ANALYSIS OF CONTEMPORARY PRINT AND WEB MEDIA ADVERTISING DESIGNS - Dash, Raimohan; Ghosh, Ramkrishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the present day, the design of advertisements for print and web media necessitates an understanding of the unique characteristics and constraints of each medium, as well as the evolving technologies and trends.